2013
DOI: 10.5038/1936-4660.6.2.2
|View full text |Cite
|
Sign up to set email alerts
|

The Geography of Financial Literacy

Abstract: This paper explores how well equipped today's households are to make complex financial decisions in the face of often high-cost and high-risk financial instruments. Specifically we focus on financial literacy. Most importantly, we describe the geography of financial literacy, i.e., how financial literacy is distributed across the fifty US states. We describe the correlation of financial literacy and some important aggregate variables, such as state-level poverty rates. Finally, we examine the extent to which d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 32 publications
(24 reference statements)
3
24
0
3
Order By: Relevance
“…These findings might suggest that financial literacy is more easily acquired via interactions with others, in the workplace or in the community. 27 Relatedly, there are also important geographic differences in financial literacy; for example, Fornero and Monticone (2011) report substantial financial literacy dispersion across regions in Italy and so does Beckmann (2013) for Romania Bumcrot, Lin, and Lusardi (2013) report similar differences across U.S. states.…”
Section: Disaggregating Financial Literacymentioning
confidence: 99%
“…These findings might suggest that financial literacy is more easily acquired via interactions with others, in the workplace or in the community. 27 Relatedly, there are also important geographic differences in financial literacy; for example, Fornero and Monticone (2011) report substantial financial literacy dispersion across regions in Italy and so does Beckmann (2013) for Romania Bumcrot, Lin, and Lusardi (2013) report similar differences across U.S. states.…”
Section: Disaggregating Financial Literacymentioning
confidence: 99%
“…The role of the environment in which people live has been investigated by a few researchers. The findings of such studies have shown that financial literacy is associated with specific features of regions of residence such as traits of urban settings (Haliassos, Jansson, and Karabulut ; Lachance ), the presence of economic distress (Bumcrot, Lin, and Lusardi ), the distribution of social capital (Guiso, Sapienza, and Zingales , ), the degree of trust in financial institutions, proxying the social capital index at a regional level (Ricci and Caratelli ), human capital (Jappelli ), and the generosity of the social security system (Jappelli ).…”
mentioning
confidence: 99%
“…While Bumcrot, Lin, and Lusardi (2013) measured the financial literacy index by using five questions about interest rates, inflation, risk diversification, the bond's price, and mortgages.…”
Section: Literature Reviewmentioning
confidence: 99%